Perspective on Computer Science Education - Yehudai, Amiram (Teaching Fundamental Concepts of Informatics, 2010)
I will present my personal perspective on Computer Science Education as I have seen it over the last three decades. Topics will include the interaction between research and education, the relation between College level curriculum and K-12 curriculum, and the role of programming languages and their influence on teaching. I will also discuss some aspects of the computer science curriculum for high-schools in Israel, which is undergoing revision.